2012
DOI: 10.4319/lo.2012.57.4.1217
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying denitrification in rippled permeable sands through combined flume experiments and modeling

Abstract: We measured denitrification in permeable sediments in a sealed flume tank with environmentally representative fluid flow and solute transport behavior using novel measurements. Numerical flow and reactive transport models representing the flume experiments were implemented to provide mechanistic insight into the coupled hydrodynamic and biogeochemical processes. There was broad agreement between the model results and experimental data. The model showed that the coupling between nitrification and denitrificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
129
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(139 citation statements)
references
References 41 publications
5
129
0
Order By: Relevance
“…The denitrification rates measured in the present study spanned the range of flow-through reactor rates (∼< 1-32 µmol L −1 h −1 ) previously observed in silicate sands (Evrard et al, 2013;Kessler et al, 2012;Marchant et al, 2014;Rao et al, 2007). The availability, and composition, of organic matter is expected to be a key factor controlling potential denitrification rates (Eyre et al, 2013a;Seitzinger, 1988), and the importance of this in permeable sediments has also been recently underscored by Marchant et al (2016), who observed a strong relationship between potential denitrification rate and sediment oxygen consumption.…”
Section: Comparison Of Potential Denitrification Rates With Previousmentioning
confidence: 99%
See 2 more Smart Citations
“…The denitrification rates measured in the present study spanned the range of flow-through reactor rates (∼< 1-32 µmol L −1 h −1 ) previously observed in silicate sands (Evrard et al, 2013;Kessler et al, 2012;Marchant et al, 2014;Rao et al, 2007). The availability, and composition, of organic matter is expected to be a key factor controlling potential denitrification rates (Eyre et al, 2013a;Seitzinger, 1988), and the importance of this in permeable sediments has also been recently underscored by Marchant et al (2016), who observed a strong relationship between potential denitrification rate and sediment oxygen consumption.…”
Section: Comparison Of Potential Denitrification Rates With Previousmentioning
confidence: 99%
“…Sites 2 and 3 in the present study seemed to deviate significantly from this relationship, as they were the only data points to lie outside the 99 % prediction interval, while site 1 sat close to the line of best fit. Omitting the study of Kessler et al (2012) still led to sites 2 and 3 being outside the prediction intervals, with site 2 being below and site 3 above the relationship observed for silicate sands. This suggests that the slope of the relationship between denitrification and oxygen consumption rate in this study differs from previous studies.…”
Section: Comparison Of Potential Denitrification Rates With Previousmentioning
confidence: 99%
See 1 more Smart Citation
“…Bottom water enters the porespace at the interface at regions of high pressure and exits at locations of lower pressure. Numerical models have further refined our understanding material transport and transformation within permeable sediments (Cardenas et al 2008;Kessler et al 2012Kessler et al , 2013. Field experiments have demonstrated that volumetric circulation within porespace can be significant (Webb and Theodor 1972;Reimers et al 2004;Hebert et al 2007;Fram et al 2014) and support the contention that advective circulation through porespace is a major determinant of shelf-scale biogeochemical processes (Rao et al 2007;Santos et al 2012a;Heuttel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On finer temporal scales, porewater flows have been shown to vary significantly on time scales on the orders of minutes (Reimers et al 2004) or less (Cardenas and Jiang 2011). In contrast, modeling (Kessler et al 2012) and experimental (e.g., Cook et al 2007, Rao et al 2007Gihring et al 2010;Gao et al 2010;Chipman et al 2012) studies of porewater geochemistry under advective conditions have been evaluated under relatively steady flow conditions. While a great improvement over static incubations (e.g., Vance-Harris and Ingall 2005), the imposition of steady-state flows and geochemical gradients within porewaters may also underestimate the rate of mineralization within a dynamic geochemical environment.…”
Section: Introductionmentioning
confidence: 99%